STRENGTHENING STUDENTS' RELIGIOUS MODERATION THROUGH ENGLISH LEARNING MATERIALS - Budiasih, Budiasih; Dewi, Fitri Ana Ika (Leksema: Jurnal Bahasa dan Sastra, 2023)
This study aims at developing English teaching materials by internalizing religious moderation for non-English students at Islamic higher education. The developed learning materials is in the form of module that is compiled based on students’ needs. This is a Research and Development (R&D) with need analysis, planning, development, revision, and production. The subjects of this study were two English lecturers of non-English study program at UIN Raden Mas Said Surakarta. The data were obtained from observation in the classrooms, interviews on Islamic moderation, and the document of English learning book. The expert judgments were applied to validate the development of the English materials. The developed materials do not only contain language competences, but also consist of some topics based on contextual learning with the basis of English for Specific Purposes (ESP) which is integrated with religious moderation values. The themes coming from students’ needs are: tolerance, respecting others, false information (hoax), helping each other, multiculturalism, and bullying. The internalization of religious moderation in developing English teaching materials is considered supportive to prevent the students from intolerance and radicalism.